STRATEGY STUDY OF TOURISM DEVELOPMENT ACEH TAMIANG REGENCY - Junita, Afrah; Ridla, Muhammad; Putra AS, Agus (RADJA PUBLIKA, 2022)
Aceh Tamiang Regency is an expansion area of East Aceh Regency. This district is located in the strategic East Sumatra route and is only approximately 136 km from the city of Medan, the capital of North Sumatra. This district is directly adjacent to the province of North Sumatra and is the gateway to enter the province of Aceh. There are 77 tourist attractions scattered in the Aceh Tamiang area, which are worth a visit. Potential tourist attractions are spread over 12 (twelve) sub-districts, both natural, cultural-historical and artificial. several problems to build tourist destinations in Aceh Tamiang Regency, including accessibility to tourism objects still looks damaged. Maintenance of damaged roads has not yet been carried out by the district government. The results of the study indicate that the position of tourism development in Tamiang Regency is in Quadrant III, meaning that tourist attraction has a very large opportunity but on the other hand faces several internal weaknesses. The strategy that can be applied in this situation is a turn-around strategy, which is a strategy to minimize weaknesses by taking advantage of existing opportunities. The focus of this strategy is to minimize internal constraints.